Accountability in Health care Services: A Study at Community Lung Health Care Center of Makassar, Indonesia - Aswan Aswan; Andi Agustang; Andi Muhammad Idkhan (Jurnal Ilmiah Ilmu Administrasi Publik, 2022)
This research is a qualitative descriptive study that aims to provide an overview of the accountability of health services at Community Lung Health Care Center of Makassar. There are eight informants as the main data source and documents as secondary data sources. Data were collected through in-depth interviews and document review. Miles and Huberman data analysis was used for data analysis. The findings revealed that there were twelve indicators of service to health services at Community Lung Health Care Center of Makassar. The results of the study examined the achievement of the realization of the indicator towards the target achieved. The obstacles found in the process of health services are the patient's lack of knowledge about health services which are offered at at Community Lung Health Care Center of Makassar, the need for a change in status to a special pulmonary hospital and increasing the capacity of human resources. There are some ways to figure out the obstacles; large-scale promotions, status change drafting teams, and training for health worker need to be held.